#### Answer

$f(3t-2)=-9t+10$

#### Work Step by Step

To find the value of $f(3t-2)$, substitute $3t-2$ to $x$ in $f(x)$ to obtain:
$f(x)=-3x+4
\\f(3t-2)=-3(3t-2)+4
\\f(3t-2) = -3(3t) +(-3)(-2)+4
\\f(3t-2)=-9t+6+4
\\f(3t-2)=-9t+10$

Published by
Pearson

ISBN 10:
013421742X

ISBN 13:
978-0-13421-742-0

$f(3t-2)=-9t+10$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.